Originally Posted by
pfarnall $\displaystyle 2(2x-4)=9-2(x+1)$
First step is to multiply out both sides to give
$\displaystyle 4x-4=9-2x-2$ (forgot to distribute the two into the -4 on the left side)
Now get all the $\displaystyle x$ terms on one side and all the non $\displaystyle x$ terms on the other, so in this case add 4 to both sides (this will remove the non $\displaystyle x$ term from the left) and add $\displaystyle 2x$ to both sides (this will remove the x term from the right) leaving
$\displaystyle 4x+2x=9-2+4$ (should be 9-2+8)
Cleaning this up gives
$\displaystyle 6x=11$ (6x=15)
and finally divide by 6
$\displaystyle x=\frac{11}{6}$ (should be $\displaystyle x = \frac{15}{6}$, which simplifies down to $\displaystyle \frac{5}{2}$)
Hopefully this is one of the answers you got.
Good luck!